An Unusual Cause of Precordial Chest Pain. (10th January 2013) - Ozkaya, Sevket; Furtun, Kamil; Yuksel, Canan; Dirican, Adem; Findik, Serhat
Abstract : Extraskeletal chondrosarcoma in anterior mediastinum is very rare. A 45-year-old male patient was admitted to the hospital with precordial chest pain. A large and well-shaped mass in the anterior mediastinum was seen radiologically, and there was a clearly compression of the heart by the mass. The lesion was totally resected, and extraskeletal mediastinal chondrosarcoma was histopathologically diagnosed. We aimed to present and discuss the radiologic, clinic, and histopathologic features of unusual presentation of extraskeletal chondrosarcoma in a case.